b - Carter, Ronald; Hughes, Rebecca; McCarthy, Michael (b, 2000)
Based entirely on real spoken and written English, this practice grammar analyses why people choose certain structures in situations and the effect of those choices on meaning.
Includes index .
Keywords: v; English language -- Problems, exercises, etc. -- Grammar; English language -- Textbooks for foreign speakers